DIALEKTIKA EPISTEMOLOGI ISLAM KLASIK DAN PENDIDIKAN AGAMA ISLAM MODERN: ANALISIS FILOSOFIS ATAS RELEVANSI PEMIKIRAN AL-GHAZALI DAN IBN RUSHD - Yono, Suyono (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
Through a philosophical examination of the thinking of AlGhazali and Ibn Rushd, this research examines the dialectics of classical Islamic epistemology and contemporary Islamic Religious Education (IRE). The study’s driving force is the epistemological issues of current IRE, which is frequently seen as normative and lacking in critical engagement, necessitating a more comprehensive philosophical framework. The goals are to analyze the dialectical connection between the two authors, describe their epistemology, and discuss its significance for contemporary IRE. Utilizing primary materials from AlGhazali and Ibn Rushd as well as pertinent secondary literature, this work adopts a philosophical-hermeneutic approach to library research. According to the findings, Ibn Rushd prioritizes rationality and the compatibility of philosophy and sharī’a, whereas AlGhazali’s epistemology combines reason and intuition (kashf) with a focus on spirituality. Their dialectics yield an inclusive epistemological framework that reconciles rational-critical and moral-spiritual components. The implication is that modern IRE can be cultivated as a middle-of-the-road, conversational, and globally relevant educational model. Theoretically, this study adds to the discussion of Islamic philosophy of education, and practically, it helps to create modern IRE curricula.